Heavy metals contamination characteristics in soil of different mining activity zones - 廖国礼 廖大学 李全明 (Transactions of Nonferrous Metals Society of China, 2008)
Depending upon the polluted features of various mining activities in a typical nonferrous metal mine, the contaminated soil area was divided into four zones which were polluted by tailings, mine drainage, dust deposition in wind and spreading minerals during vehicle transportation, respectively. In each zone, soil samples were collected. Total 28 soil samples were dug and analyzed by ICP-AES and other relevant methods. The results indicate that the average contents of Zn, Pb, Cd, Cu and As in soils are 508.6, 384.8, 7.53, 356 and 44.6 mg/kg, respectively. But the contents of heavy metals in different zone have distinct differences. The proportion of oxidizing association with organic substance is small. Difference of the association of heavy metals is small in different polluted zones.